2021
DOI: 10.3390/w13182466
|View full text |Cite
|
Sign up to set email alerts
|

Transpiration and Water Use of an Irrigated Traditional Olive Grove with Sap-Flow Observations and the FAO56 Dual Crop Coefficient Approach

Abstract: The SIMDualKc model was applied to evaluate the crop water use and the crop coefficient (Kc) of an irrigated olive grove (Olea europaea L.) located in Sicily, Italy, using experimental data collected from two crop seasons. The model applies the FAO56 dual Kc approach to compute the actual crop evapotranspiration (ETc act) and its components, i.e., the actual tree transpiration (Tc act), obtained through the basal crop coefficient (Kcb), and soil evaporation according to an evaporation coefficient (Ke). Model c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 55 publications
6
11
0
Order By: Relevance
“…The reported goodness-of-fit indicators for the E1 and E2 experiments are within the ranges of values reported in the literature for the SIMDualKc simulations of perennial crops for vineyards [67,[76][77][78], peach orchards [42], and olive groves [66,79,80]. They are also similar to those reported by Darouich et al [52,53] for horticultural crops grown in the same edapho-climatic conditions in the Akkar plain.…”
Section: Eer Review 15 Of 29supporting
confidence: 86%
See 1 more Smart Citation
“…The reported goodness-of-fit indicators for the E1 and E2 experiments are within the ranges of values reported in the literature for the SIMDualKc simulations of perennial crops for vineyards [67,[76][77][78], peach orchards [42], and olive groves [66,79,80]. They are also similar to those reported by Darouich et al [52,53] for horticultural crops grown in the same edapho-climatic conditions in the Akkar plain.…”
Section: Eer Review 15 Of 29supporting
confidence: 86%
“…For Experiment 1 (2007Experiment 1 ( -2011, an Fr of 0.55 was adopted for all crop stages, which corresponds to the upper value suggested for medium density and height of citrus trees. For Experiment 2, an Fr value of 0.61 was assumed, corresponding to the central value of The reported goodness-of-fit indicators for the E1 and E2 experiments are within the ranges of values reported in the literature for the SIMDualKc simulations of perennial crops for vineyards [67,[76][77][78], peach orchards [42], and olive groves [66,79,80]. They are also similar to those reported by Darouich et al [52,53] for horticultural crops grown in the same edapho-climatic conditions in the Akkar plain.…”
Section: Simdualkc Vs Aandp Approachsupporting
confidence: 54%
“…Issues related to the quality of the measured dataset and the empirical one-dimensional modeling approach used here to describe the soil water balance in a three-dimensional drip irrigation system may also help explaining why the goodness-of-fit indicators are not as high as in former studies, e.g., Paço et al [88]. Nevertheless, the reported goodness-of-fit indicators are within the range of values reported in the literature for soil water content simulations of field crops [89,90], vegetable crops [91,92], and perennial crops [58][59][60][61] using the same model.…”
Section: Model Performancesupporting
confidence: 52%
“…Examples of applications to vine and fruit crop systems can be found in the recent literature review provided by Rallo et al [53] and Pereira et al [56]. The SIMDualKc model [57] has adopted the dual-K c approach for estimating daily ET fluxes of crops grown under different climatic regions and management practices, including grapevine [46,47,58], peach [59], and olive [60,61]. Yet, despite the growing use of the FAO56 dual-K c approach for computing crop evapotranspiration fluxes and improving soil water management in complex agricultural systems, there is still the need for extending research focusing on the search for standard K c and K cb values as well the impact of active ground cover, cover crops, and mulches on crop evapotranspiration of vine systems [53].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the K c values for the mid-season, when soil evaporation and weed transpiration were limited, resulted lower than the segments relative to the late and the non-growing seasons, in which rainfall and evapotranspiration from the soil surface occur. Similar annual patterns of crop coefficient have been recently reported by Puig-Sirera et al ( 2021a ) for an olive orchard and by Segovia-Cardozo et al ( 2021 ) in a citrus orchard in which, focusing on the full year and not only on the growing season, it was observed that K c values in non-growing periods resulted in higher values than in the growing period, due to the large contribution of soil evaporation.…”
Section: Discussionsupporting
confidence: 87%